Structural and seismographic characteristics of a sector of the Magdalena Shelf, western margin of Baja California, Mexico, from 2D seismic reflection profiles - Gómez Ávila, Marianggy Del Carmen (2021)
The Magdalena Shelf, located on the Pacific margin of Baja California, Mexico, is crosscut by the Tosco-Abreojos transform fault system, while the Santa Margarita and San Lazaro faults are sub-parallel and located east of the shear zone that cuts the continental slope longitudinally. Processing and interpretation 2D multichannel marine reflection seismic data show evidence for the structural deformation and seismostratigraphic characteristics of a sector of the shelf. This study allowed mapping unknown faults, of which the two main ones are named Iray and Magdalena Faults. San Lazaro fault has a strike of N 15° W and length of 70 km, with an apparent dip of ~ 42° to the NE. The San Lazaro fault controls the western flank of the basin of the same name forming a semi-graben of 20 km wide and its sedimentary fill of ~ 4.5 km in thickness. The Iray-Magdalena basin has a depth of~4.0 km. We identified six seismic stratigraphic sequences, and two main discordances, which are considered to be regional discordances. One of which is the Cretaceous-Paleogene discordance, and the other corresponds to the Miocene discordance, which has been considered an important geological marker of the tectonic evolution of region. Acoustic basement defines a structural high parallel to the continental slope and aligned with outcrops of the ophiolite complex. The zone of active deformation of the Tosco-Abreojos fault system is between 15 and 18 km wide. This region may contain previously unknown structures and can represent a geological/seismic risk, which can have not only scientific implications, but also social impact in the communities of the region.